2020
DOI: 10.3390/ani10122303
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Protein Hydrolysates from Anchovy (Engraulis Encrasicolus) Waste for Twelve Weeks Decreases Metabolic Dysfunction-Associated Fatty Liver Disease Severity in ApoE–/–Mice

Abstract: Metabolic dysfunction-associated fatty liver disease (MAFLD) includes several diseases, ranging from simple steatosis to steatohepatitis, fibrosis and cirrhosis. Fish-rich diets are considered helpful in the prevention of MAFLD, and the enzymatic hydrolysis of fish waste has been explored as a means of obtaining high-value protein hydrolysates, which have been proven to exert beneficial bioactivities including anti-obesity and hypocholesterol effects. This study aimed to assess the effect of the administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Soybeans are an important dietary source because they contain high-quality proteins and are rich in bioactive compounds such as isoflavones and saponins [ 1 ]. Nowadays, diet supplementation has been widely accepted as a useful strategy to modulate biochemical and molecular pathways to improve physiological and pathological conditions [ 2 , 3 ]. It has been reported that soybeans have many therapeutic properties, including hypocholesterolemic [ 4 ], anti-hypertensive [ 5 ], and anti-cancer effects [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soybeans are an important dietary source because they contain high-quality proteins and are rich in bioactive compounds such as isoflavones and saponins [ 1 ]. Nowadays, diet supplementation has been widely accepted as a useful strategy to modulate biochemical and molecular pathways to improve physiological and pathological conditions [ 2 , 3 ]. It has been reported that soybeans have many therapeutic properties, including hypocholesterolemic [ 4 ], anti-hypertensive [ 5 ], and anti-cancer effects [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These repercussions highlight the need for a smooth transition from prepartum to postpartum period for optimal dairy cow health and performance. The improvement of diet composition becomes a key factor to improve the health status and welfare of animals [5], as well as to enhance productivity in livestock [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Six-month-old female B6.129P2-ApoE −/− mice (C57BL/6 genetic background), enrolled in previous studies carried out by of our research group [ 25 , 26 ], were used in this experimental trial. Mice were allocated to sterile filter-top cages and kept on a 12-h light/dark cycle, in standard laboratory conditions (21 ± 1 °C, 55 ± 5% humidity).…”
Section: Methodsmentioning
confidence: 99%
“…The anchovy ( Engraulis encrasicolus ) is a common fish species of the Mediterranean Sea, known to produce high-value bioactive peptides under enzymatic hydrolysis, with nutraceutical potential only partially explored to date [ 24 ]. A recent survey carried out by our research group demonstrated that 12-week administration of 10% ( w/w ) anchovy protein hydrolysates (APH) in a high-fat diet produced a significant anti-obesity effect, improving lipid metabolism and reducing hepatic steatosis and liver damage in ApoE −/− mice [ 25 ]. Additionally, APH significantly produced anti-inflammatory and antioxidant effects, downregulating the expression of pro-inflammatory cytokines and modulating the expression of oxidative stress-related genes in the aorta and heart tissue in the same ApoE −/− mice [ 26 ].…”
Section: Introductionmentioning
confidence: 99%